Platysma transverse myocutaneous flap: a 21 case series of an overlooked reconstructive method for facial skin defects - Girardi,Fábio Muradás (2021)
Abstract Introduction Since the first report of a platysma transverse myocutaneous flap in 1977, few articles about this flap design have been added to the literature. Objective Our aim is to describe our department's experience with platysma transverse myocutaneous flap. Methods A retrospective review of all patients undergoing platysma transverse myocutaneous flap reconstruction between 2011 and 2019. Results There were 16 men and 5 women in this series. The mean patients' age was 72.7 years old. In eight cases, we had wound complications, including four wound infections, one hematoma and three distal flap ischemia problems. Distal flap ischemia occurred only in cases that advanced beyond the midline and with length-to-width ratio equal to or over three to one. Neck dissection was performed in two of these three cases with ischemic complications. Conclusion Several factors may influence platysma transverse myocutaneous flap survival. Usually a long and narrow flap, especially crossing the neck midline and associated with neck dissection are more prone to poor outcomes.